FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PT. BANK RAKYAT INDONESIA (PERSERO) Tbk - Aldo Aulia; Novie Al Muhariah; Andri Irawan (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2024)
The aim of this research is to determine the influence of the Return of Assets (ROA), Return of Equity (ROE) and Earning Per Share (EPS) factors on the share price of PT. Bank Rakyat Indonesia (Persero) Tbk . The method used in this research is Multiple Regression. The amount of data used in this research was 15 samples.The research results show that simultaneously Return Of Assets (ROA), Return Of Equity (ROE) and Earning Per Share (EPS) have a significant effect on PT's share price. Bank Rakyat Indonesia (Persero) Tbk.. Partially, the Return of Assets (ROA) variable has no significant effect, the Return of Equity (ROE) variable has a significant effect and the Earning Per Share (EPS) variable has no significant effect on PT's share price. Bank Rakyat Indonesia (Persero) Tbk 2008-2022. The Determination Coefficient value is (Adjusted R Square) 0.801. This shows that the percentage contribution of the influence of Return Of Assets (ROA), Return Of Equity (ROE) and EPS on PT Share Prices. Bank Rakyat Indonesia (Persero) Tbk for is 80.10%. Meanwhile, the remaining 19.90% is influenced by other variables not included in this research model.